Potensi Ekstrak Etanol Daun Pepaya Emas (Carica Papaya L) Sebagai Antihipertensi dan Nefroprotektif: In Vivo - Miming Andika; Thesa Fitri Yatiningsih; Yuliarti; Rizqa Hasanah (JURNAL FARMASI DAN MAKANAN, 2025)
Hypertension is a condition in which the systolic blood pressure is above 140 mmHg and the diastolic blood pressure is above 90 mmHg. Kidney failure is a progressive, irreversible disorder of renal function, in which kidney function declines in maintaining metabolism, fluid, and electrolyte balance, resulting in uremia. The purpose of this study was to determine the effectiveness of ethanol extract of papaya leaves (Carica papaya L) in reducing blood pressure and serum creatinine levels in male white rats. This study was experimental in nature, using 60 rats divided into 12 groups, namely negative control, positive control, comparison group (captopril), and dose groups (100, 200, 400 mg/kg body weight). The inducer used for hypertension was 8% NaCl and the inducer for kidney failure was CCl4. Blood pressure measurements were carried out using a Non-Invasive Blood Pressure (NIBP) device, and the measurement of serum creatinine levels was performed using a photometer. Data analysis was conducted using One Way ANOVA followed by Duncan's test. The results showed that the administration of papaya leaf ethanol extract significantly affected the reduction of blood pressure and serum creatinine levels (p<0.05). It can be concluded that the most effective dose for lowering blood pressure is 400 mg/kg body weight, and the most effective dose for reducing serum creatinine levels is 100 mg/kg body weight.